2009
DOI: 10.1353/sof.0.0269
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Origin and Host Country Schooling on the Economic Performance of Immigrants

Abstract: This study examines the economic returns to schooling acquired in the country of origin and the country of destination. It uses large-scale survey data on Turkish, Moroccan, Surinamese and Antillean immigrants in the Netherlands, which contain direct measures of pre-and post-migration schooling. It is studied whether the returns to origin-country schooling depend on contextual factors: i.e., immigrant group and the region of living. Furthermore, we examine the importance of host-country schooling for labor mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 55 publications
3
126
0
3
Order By: Relevance
“…We interpret this finding as being the consequence of the family migratory strategies of the women who arrived without their partner, and who accepted work in domestic services because was the easiest way to regularise their situation and save money in order to facilitate future family reunification processes. The analysis also indicated that it was not just the presence of the partner that mattered, but also his country of origin, as having contact with natives may play a particularly important role in an immigrant's labour market status (Kanas and Van Tubergen 2009). Our results confirmed our assumption that a woman with a Spanish-born partner would have had a much higher likelihood of abandoning domestic and cleaning work.…”
Section: 6%supporting
confidence: 79%
See 1 more Smart Citation
“…We interpret this finding as being the consequence of the family migratory strategies of the women who arrived without their partner, and who accepted work in domestic services because was the easiest way to regularise their situation and save money in order to facilitate future family reunification processes. The analysis also indicated that it was not just the presence of the partner that mattered, but also his country of origin, as having contact with natives may play a particularly important role in an immigrant's labour market status (Kanas and Van Tubergen 2009). Our results confirmed our assumption that a woman with a Spanish-born partner would have had a much higher likelihood of abandoning domestic and cleaning work.…”
Section: 6%supporting
confidence: 79%
“…Skills learned in the country of origin may be difficult to transfer, especially if the immigrant has a weak understanding of the labour market norms and the language of the host society (Chiswick 1978;Chiswick, Lee, and Miller 2005;Clark and Drinkwater 2008;Kanas et al 2012). A key factor in determining the labour market performance of new immigrants is the extent to which their education, pre-migration labour market experience, and training obtained abroad are valued at the destination (Blackaby et al 2002;Kee, 1995;Clark and Drinkwater 2008;Kanas and Van Tubergen 2009). Moreover, other researchers stressed the importance of proficiency in the host country language in explaining the employment levels immigrants attain at the country of destination, as having better language skills increases the range of jobs in the labour market for which immigrants are qualified (Leslie and Lindley 2001;Dustmann and Fabbri 2003;Berman, Lang, and Siniver 2003;Bleakley and Chin 2004).…”
Section: Theoretical Perspectives and Research Hypotheses 21 Theoretmentioning
confidence: 99%
“…Previous studies have shown that immigrants and refugees get relatively limited returns to the educational qualifications obtained in the origin country, which leads to feelings of underemployment (Kanas & Van Tubergen, 2009). When the quality of employment in the host country is below migrants' educational standards and their level of pre-migration employment, this may result in feelings of relative deprivation rather than integration in the host country.…”
Section: Discussionmentioning
confidence: 99%
“…La distancia económica, social y cultural determinará en gran medida la cantidad y el grado de https://doi.org/10.3989/ris.2018.76.1. 15.192 transferibilidad a un nuevo país, al igual que sucede con las credenciales educativas (Kanas y Van Tubergen 2009;Kanas y Van Tubergen 2014). Para el caso español, podemos esperar que los inmigrantes con países intermedios desarrollados tengan un mayor rendimiento en España de su experiencia migratoria que los que han residido en países en desarrollo.…”
Section: La Singularidad De Los Inmigrantes Sucesivosunclassified